Collaboration of Serbia in work of Ph. Eur. and OMCL network: results, activities and future - Ubavić, Stana; Malešević, Marija; Krajnović, Dušanka (Archives of Pharmacy, 2022)
European pharmacopoeia (Ph. Eur.) is unique reference for quality of medicines in Europe (First issue, 1969). Collaboration of Serbia is done through expert groups, participation at Ph. Eur. Commission, quality control of medicines in National Control laboratory (NKL), and network of Official medicines control laboratories (OMCL). The aim of work was to present historical data on the collaboration between Serbia, Ph. Eur. and OMCL, by searching data from ALIMS database, which coordinates this collaboration. Collaboration started in 1991. when Yugoslavia ratified Convention on Ph. Eur. As an independent state, Serbia was participating in the work of Ph.Eur. Commission since 2003. Serbia has 7 representatives in expert groups: 10B,11 (Organic Chemistry), 15 (Human Vaccines and Sera), P4 (Patent medicines), PaedF (Pediatric Formulas), POW (Powders) and ST (Standard Terms). These experts have developed 16 new monographs, European Pediatric Formulas and participated in revision of over 10 existing monographs. Representatives of Serbia chair P4 and POW groups. NKL is a full member of the OMCL network since 2004, and in 2013 it was certified against ISO 17025. Since 2006, NKL was participating in the development of new chemical reference substances (CRS), monitoring their quality, doing laboratory performance studies, European systematic drug quality control and studies of suspicious and unknown samples. By active participation in development of monographs and quality control of medicines, the competence of experts has been improved. By application of the modern technologies this has enabled patients in Serbia to have available medicines of equivalent quality as on the EU market.